2017
DOI: 10.1177/1932296817748964
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Glucose Monitoring in Preventing Inpatient Hypoglycemia in General Wards: The Glucose Telemetry System

Abstract: This pilot study indicates that the use of CGM values in hospitalized patients can be successfully transmitted to a monitoring device in the nursing station, improving patient surveillance in insulin treated patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…POC glucose testing was not completely eliminated, and sensor values were used to aid in deciding corrective insulin coverage only. Our pilot data, although small in number, support the use of CGM in noncritically ill patients, similar to previous studies (1)(2)(3). We found efforts needed to be invested in ensuring smooth operation of the system.…”
supporting
confidence: 83%
“…POC glucose testing was not completely eliminated, and sensor values were used to aid in deciding corrective insulin coverage only. Our pilot data, although small in number, support the use of CGM in noncritically ill patients, similar to previous studies (1)(2)(3). We found efforts needed to be invested in ensuring smooth operation of the system.…”
supporting
confidence: 83%
“…A remarkable consistency between CGM and BG measurements was reported without differences between groups, with 99% of data points in the clinically accurate or acceptable Clarke error grid zones, and the relative numbers of correctly identified episodes of glucose <3.9 and >13.9 mmol/L detected by CGM (sensitivity) were 47.3% and 81.5%, respectively. The number of hypoglycemic episodes (3.3 to <3.9 mmol/L) during nighttime detected by CGM (compared with values from the BG measurements) was 15-fold higher, and the number of episodes >13.9 mmol/L detected by CGM during nighttime was 12.5-fold higher (94) compared with capillary POC glucose testing in general medicine patients with T2D treated with a basal-bolus insulin regimen for ≥3 days. In addition, the use of CGM, compared with POC testing, uncovered a greater number of hypoglycemic events, and 60% of the episodes were during the night.…”
Section: Cgmmentioning
confidence: 95%
“…In addition, hypoglycemia alarms are only visible and audible at the bedside; as a result, nurses need to frequently enter the patient’s room to monitor glucose values on the CGM receiver. To overcome these limitations, a recent promising pilot study reported on the feasibility of a continuous glucose telemetry system in high hypoglycemia–risk patients in non-ICU settings (94). Elderly patients receiving high-dose insulin treatment and with multiple comorbidities were included in this study.…”
Section: Cgmmentioning
confidence: 99%
“…Spanakis et al . used CGM in general medicine in people with insulin‐treated Type 2 diabetes and the results were transmitted to a central nursing station monitoring system. An alarm system was set up at glucose <4.7 mmol/l.…”
Section: Prevention Of Inpatient Hypoglycaemiamentioning
confidence: 99%